Analysis of the sex ratio of reported gonorrhoea incidence in Shenzhen, China. Issue 3 (14th March 2016) - Xiong, Mingzhou; Lan, Lina; Feng, Tiejian; Zhao, Guanglu; Wang, Feng; Hong, Fuchang; Wu, Xiaobing; Zhang, Chunlai; Wen, Lizhang; Liu, Aizhong; Best, John McCulloch; Tang, Weiming
Abstract : Objective: To assess the clinical process of gonorrhoea diagnosis and report in China, and to determine the difference of sex ratio between reported incidence based on reporting data and true diagnosis rate based on reference tests of gonorrhoea. Setting: A total of 26 dermatology and sexually transmitted disease (STD) departments, 34 obstetrics-gynaecology clinics and 28 urology outpatient clinics selected from 34 hospitals of Shenzhen regarded as our study sites. Participants: A total of 2754 participants were recruited in this study, and 2534 participants completed the questionnaire survey and provided genital tract secretion specimens. There were 1106 male and 1428 female participants. Eligible participants were patients who presented for outpatient STD care at the selected clinics for the first time in October 2012 were at least 18 years old, and were able to give informed consent. Outcome measures: Untested rate, true-positive rate, false-negative rate and unreported rate of gonorrhoea, as well as reported gonorrhoea incidence sex ratio and true diagnosis sex ratio were calculated and used to describe the results. Results: 2534 participants were enrolled in the study. The untested rate of gonorrhoea among females was significantly higher than that among males (female 88.1%, male 68.3%, p=0.001). The male-to-female sex ratios of untested rate, true-positive rate, false-negative rate and unreported rate were 1:1.3, 1.2:1, 1:1.6 and 1:1.4, respectively. The reported gonorrhoea incidence sex ratio of new diagnosed gonorrhoea was 19.8:1 (male vs female: 87/1106 vs 5/1420), while the true diagnosis sex ratio was 2.5:1 (male vs female: 161/1106 vs 84/1420). These data indicate that the sex ratio of reported gonorrhoea incidence has been overestimated by a factor of 7.9 (19.8/2.5). Conclusions: We found the current reported gonorrhoea incidence and sex ratios to be inaccurate due to underestimations of gonorrhoea incidence, especially among women.